Hubungan Tingkat Pengetahuan Dengan Kepatuhan Pemakaian Alat Pelindung Diri Petugas Cleaning Service Di Rumah Sakit Umum Bangli Tahun 2019 - Ni Made Warmuni; Ni Ketut Rusminingsih (Poltekkes Kemenkes Denpasar, 2020)
Abstract, Cleaning service personnel in working in hospitals are not fully equipped with personal protective equipment or do not adhere to using personal protective equipment so as to cause workplace accidents. This study aims to determine the relationship between the level of knowledge and compliance with the use of personal protective equipment cleaning service officers at Bangli General Hospital. The instrument used was a questionnaire containing a statement of knowledge about personal protective equipment and a checklist of observations about the complete use of personal protective equipment. The type of research used in this study is the cross sectional approach. Samples were taken with a total sample population of 36 cleaning service officers working at Bangli General Hospital. Research analysis uses univariate analysis for the level of knowledge and compliance with the use of personal protective equipment. Bivariate analysis using the chi-square statistical test and contingentcy coefficient. The results of the study showed that there was a relationship between the level of knowledge and compliance with the use of cleaning service personal protective equipment (p = 0.001; a = 0.05). The cleaning service officer is expected to comply with the standard operating procedures for the use of personal protective equipment so that safety and security are created in work and the application of occupational safety and health to the hospital cleaning service personnel.